Highly organosoluble and transparent polyamides containing cyclohexane and trifluoromethyl moieties: Synthesis and characterization (eXPRESS Polymer Letters)
New aromatic diamine with cyclohexane moiety substituted with trifluoromethyl group in the side chain, 4,4’-(cyclohexane-1,4-diylbis(oxy))bis(3-(trifluoromethyl)aniline) (2), was successfully synthesized through the Williamson reaction of 1,4-cyclohexanediol and 2-chloro-5-nitrobenzotrifluoride, to yield the intermediate dinitro compound 1, followed by catalytic reduction with hydrazine and Pd/C to afford the diamine 2. This diamine monomer leads to a series of organic-soluble polyamides (4a–d) when reacted with different commercially available aromatic diacids (a–d) via a direct polycondensation with triphenyl phosphite and pyridine. The resulting polymers had inherent viscosities ranging from 0.89 to 1.29 dl/g. All the polymers showed outstanding solubility and could be easily dissolved in amide-type polar aprotic solvents and even dissolved in less polar solvents. All the polymers formed transparent, strong, and flexible films with tensile strengths of 54–68 MPa, Young’s moduli of 1.6–1.9 GPa, and elongations at break of 13.3–15.5%. These polyamide films have low dielectric constants of 2.15–2.88 at 1 MHz and low water absorptions of 1.96–2.84%. Wide-angle X-ray diffraction measurements revealed that these polyamides were amorphous in nature.